Network Analysis of Intercity Bus Terminal and Inner-City Toll Road Development – The Case of Bandung City - Ayuningtyas, Kardina; Frazila, Russ; Wibowo, Sony; Weningtyas, Widyarini; Farda, Muhammad (http://dx.doi.org/10.31427/IJSTT.2019.2.1.2, 2019)
This paper explores the impact of Gedebage Terminal development to traffic performance in Bandung City, as well as the development of the inner-city toll road that connects eastern and western part of Bandung City. In addition, the study also analyzes the potential of minibus / public transport route that connects three terminals, namely Gedebage, Cicaheum and Leuwipanjang Terminal, in Bandung City. The study is carried out by using the 4-step modeling principle, by utilizing EMME/4 software. According to the analysis, the development of inner-city toll road will impact the city’s road performance significantly. On the other hand, the development of Gedebage Terminal as a terminal that serves intercity travel replacing Cicaheum Terminal will influence road network performance around the terminal in terms of traffic flow, vehicle speed and volume capacity ratio. The analysis results also suggest that the addition of public transport fleet with high capacity, such as bus, that connects the bus terminals is necessary to support public transport performance in Bandung City.